Chemoradiation in patients with unresectable extrahepatic and hilar cholangiocarcinoma or at high risk for disease recurrence after resection: analysis of treatment efficacy and failure in patients receiving postoperative or primary chemoradiation = Radiochemotherapie bei Patienten mit extrahepatischen und hilären Gallengangskarzinomen nach inkompletter Resektion oder Inoperabilität : Evaluierung von Effektivität, Toxizität und Rezidivmustern nach postoperativer oder primärer Radiochemotherapie - Habermehl, Daniel; Lindel, Katja; Rieken, Stefan; Goeppert, Benjamin; Büchler, Markus W.; Schirmacher, Peter; Welzel, Thomas; Debus, Jürgen; Combs, Stephanie (Strahlentherapie und Onkologie, 2012)
BackgroundThe purpose of this work was to determine efficacy, toxicity, and patterns of recurrence after concurrent chemoradiation (CRT) in patients with extrahepatic bile duct cancer (EHBDC) and hilar cholangiocarcinoma (Klatskin tumours) in case of incomplete resection or unresectable disease.Patients and methodsFrom 2003-2010, 25 patients with nonmetastasized EHBDC and hilar cholangiocarcinoma were treated with radiotherapy and CRT at our institution in an postoperative setting (10 patients, 9 patients with R1 resections) or in case of unresectable disease (15 patients). Median age was 63 years (range 38-80 years) and there were 20 men and 5 women. Median applied dose was 45 Gy in both patient groups.ResultsPatients at high risk (9 times R1 resection, 1 pathologically confirmed lymphangiosis) for tumour recurrence after curative surgery had a median time to disease progression of 8.7 months and an estimated mean overall survival of 23.2 months (6 of 10 patients are still under observation). Patients undergoing combined chemoradiation in case of unresectable primary tumours are still having a poor prognosis with a progression-free survival of 7.1 months and a median overall survival of 12.0 months. The main site of progression was systemic (liver, peritoneum) in both patient groups.ConclusionChemoradiation with gemcitabine is safe and can be applied safely in either patients with EHBDC or Klatskin tumours at high risk for tumour recurrence after resection and patients with unresectable tumours. Escalation of systemic and local treatment should be investigated in future clinical trials.
Gesehen am 10.10.2018